Efficacy, safety and immunogenicity of etanercept biosimilars versus reference biologics in patients with rheumatoid arthritis: A meta-analysis - Rui Hu; Tao Yuan; Hui Wang; Jianglin Zhao; Liya Shi; Quankai Li; Chunmei Zhu; Chunmei Zhu; Na Su; Na Su; Shengzhao Zhang (Frontiers Media S.A., 2023)
Background: Although with the application of etanercept biosimilars in the field of rheumatoid arthritis, the evidences of their efficacy, safety, and immunogenicity are still limited. We conducted this meta-analysis to evaluate the efficacy, safety and immunogenicity of etanercept biosimilars for treating active rheumatoid arthritis compared to reference biologics (Enbrel®).Methods: PubMed, Embase, Central, and ClinicalTrials.gov were searched for randomized controlled trials of etanercept biosimilars treated in adult patients diagnosed with rheumatoid arthritis from their earliest records to 15 August 2022. The outcomes included ACR20, ACR50, and ACR70 response rate at different time points from FAS or PPS, adverse events, and proportion of patients developed anti-drug antibodies. The risk of bias of each included study was assessed using the revised Cochrane Risk of Bias in Randomised Trials tool, and the certainty of evidence was rated according to the Grading of Recommendation Assessment, Development, and Evaluation.Results: Six RCTs with 2432 patients were included in this meta-analysis. Etanercept biosimilars showed more benefits in ACR50 at 24 weeks from PPS [5 RCTs, OR = 1.22 (1.01, 1.47), p = 0.04, I2 = 49%, high certainty], ACR50 at 1 year from PPS [3 RCTs, OR = 1.43 (1.10, 1.86), p < 0.01, I2 = 0%, high certainty] or FAS [2 RCTs, OR = 1.36 (1.04, 1.78), p = 0.03, I2 = 0%, high certainty], and ACR70 at 1 year from PPS [3 RCTs, OR = 1.32 (1.01, 1.71), p = 0.04, I2 = 0%, high certainty]. In terms of other outcomes about efficacy, safety, and immunogenicity, the results showed that there was no significant difference between etanercept biosimilars and reference biologics, and the certainty of evidences ranged from low to moderate.Conclusion: Etanercept biosimilars showed more benefits in ACR50 response rate at 1 year than reference biologics (Enbrel®), other outcomes for clinical efficacy, safety, and immunogenicity of etanercept biosimilars were comparable with originator in patients with rheumatoid arthritis.Systematic Review Registration: PROSPERO, identifier CRD42022358709